PERAN SEARCH ENGINE OPTIMIZATION (SEO) PADA WEBSITE TERHADAP BRAND AWARENESS DAN KINERJA CV FORNEO TOMITA - Ismadi, Putu Berhan Natha; Heptariza, Anita; Ramayu, I Made Satrya (Universitas Dharmawangsa, 2025)
According to the Ministry of Communication and Information, data on the development of print media, radio, television, and cyber over the past ten years shows that modern society tends to prefer interactive, personal, and real-time content. This study uses a qualitative method with a narrative approach, because this method allows researchers to explore the experiences of research informants in depth. The grand theory in this study uses attention economy theory. The research findings show that the implementation of SEO is a company's step in responding to the digitalization era and an effort to win the competition for publication media and in its implementation itself there is a big initiative from the owner to start digitalization in terms of publication. In addition, Search Engine Optimization (SEO) also has a positive impact on brand awareness where there is an increase in the visibility of website pages in search engines, this success cannot be separated from the collaboration between divisions in the company in terms of publication. However, there are also challenges that must be faced, namely changes in the habits of digital page users where users tend to prefer watching short videos or scrolling social media rather than reading website writing on the internet. The internal performance of the team in the company is also affected by the implementation of Search Engine Optimization (SEO), namely the selection of keywords and main topics of discussion in the content, on the other hand this also has a positive impact on user experience and audience preferences.